A Study of Social Factors Associated with the Use of Information and Communication Technology: A Case Study of High School Female Students in Yazd - Fatemeh Teymouri; Masoud Hadjizadeh Meimandi; Akbar Zare Shahabadi (Shiraz University of Medical Sciences, 2018)
Background: Use of modern communication technologies by teachers and students is an inventible strategy in educational centers. The aim of this study is to evaluate the social factors involved in using modern means of communication by female high school students in the city of Yazd, Iran. Methods: The present research is a cross-sectional study conducted in 2015. As many as 365 girl students selected through a multiple-stage cluster sampling method took a researcher-made questionnaire that studied demographic characteristics and evaluated the extent of using modern communication technologies such as computer software programs, the Internet network, mobile phones, and social networks. The investigated social factors were age, family dimension, school type, family income, and parents' education. Results: The findings showed that the use of modern communication technologies by students with mean 39.3 was lower than average, while computer software had a mean of 37.9, the Internet with a mean of 37.6, networks social media with a mean of 31.6, which was less than average, and mobile phone with a mean of 56 was higher average that, this difference is statistically significant(P < 0.001). Variables such as school type (P < 0.001), parents' education (P < 0.001), and family income (P = 0.04) had a significant correlation with the extent of using modern communication technologies (P < 0.05), while age and family dimension proved to have no correlation in this regard. Conclusions: Use of modern communication technologies is associated with family income and parents' education. It means that an increase in parents' education and family income will lead to a higher level of skills in using these technologies. Educational policy makers should provide the poor segment of the society with an access to modern technologies. Attention to the risks of social networks is also recommended.